Evaluation of the Effect of Captopril and Losartan on Tacrolimus-induced Nephrotoxicity in Rats - Poormoosavi, Seyedeh Mahsa; Behmanesh, Mohammad Amin; Abeyat, Hamed; Sangtarash, Ehsan (Drug Research, 2021)
Background Tacrolimus is an immunosuppressive drug. Activation of the renin-angiotensin system (RAS) and associated inflammations may exacerbate the toxic effects of tacrolimus. Given the significant role of the kidney in RAS this study aimed to evaluate the effect of captopril as an angiotensin-converting enzyme (ACE) blocker and losartan as an angiotensin II receptor blocker on tacrolimus-induced nephrotoxicity.Materials and Methods In total, 36 adult male rats weighing 200–250 gr were completely randomized and divided into six groups (control, tacrolimus, tacrolimus and losartan, tacrolimus and captopril, losartan, and captopril) for 30 days. Afterwards, blood urea nitrogen (BUN), creatinine (Cr) and ACE2 enzyme were measured. Also, both kidneys were collected for histological examinations.Results The level of BUN and Cr significantly increased in tacrolimus group. The level of BUN and Cr were lower in the groups treated with a combination of tacrolimus and losartan or captopril. While ACE2 level increased in the groups receiving a combination of tacrolimus and losartan or captopril, the level of increase was insignificant, compared to the group treated with tacrolimus alone. The glomerulus diameter and the thickness of the renal proximal tubular epithelium significantly decreased in the group treated with tacrolimus alone. the mentioned variables increased in the group treated with a combination of tacrolimus and losartan or captopril, compared to the tacrolimus group.Conclusion According to this study, tacrolimus increased the BUN and Cr levels while decreasing the ACE2 levels. However, tacrolimus in combination with losartan or captopril seemed to decrease the nephrotoxicity of the drug.
Keywords: tacrolimus; losartan; captopril; nephrotoxicity; rat